2022
DOI: 10.3390/curroncol29030143
|View full text |Cite
|
Sign up to set email alerts
|

Report from the Ready for the Next Round Thought-Leadership Roundtables on Building Resilience in Cancer Care and Control in Canada-Colorectal Cancer Canada; 2021

Abstract: (1) Background: The COVID-19 pandemic illuminated vulnerabilities in the Canadian health care system and exposed gaps and challenges across the cancer care continuum. Canada is experiencing significant disruptions to cancer-related services, and the impact these disruptions (delays/deferrals/cancellations) have on the health care system and patients are yet to be determined. Given the potential adverse ramifications, how can Canada’s health care systems build resilience for future threats? (2) Methods: To answ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The joint action of professional and experiential expertise may represent a mitigation strategy to responsiveness gaps, which in turn reduces adversity. In a report from leadership roundtables, one solution to move toward a more resilient healthcare system was patient-centricity as an approach "that will give the health care system, the resilience it needs" [3] (p. 1735). The symposium proposed a step forward, highlighting the patient's role in contributing to HCP resilience.…”
Section: The Patient's Role In Improving Cancer Team Resiliencementioning
confidence: 99%
See 2 more Smart Citations
“…The joint action of professional and experiential expertise may represent a mitigation strategy to responsiveness gaps, which in turn reduces adversity. In a report from leadership roundtables, one solution to move toward a more resilient healthcare system was patient-centricity as an approach "that will give the health care system, the resilience it needs" [3] (p. 1735). The symposium proposed a step forward, highlighting the patient's role in contributing to HCP resilience.…”
Section: The Patient's Role In Improving Cancer Team Resiliencementioning
confidence: 99%
“…Adversity arises from daily exposure to the suffering of patients, heavy workload and time pressures, workforce shortages, and administrative burdens [1]. The lengthy and profound disruption produced by the COVID-19 pandemic compounded a longstanding cancer crisis [2], aggravating scarcities of material and human resources and the siloed functioning of cancer care provision [3,4]. Consequently, oncology HCPs experience more stressful situations, are more dissatisfied with their work life, and more susceptible to physical and psychological problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[38][39][40] As such, these combined stressors significantly reduce workrelated capacities including a decrease in team members' performance, deterioration in communication and teamwork and limited collaborative decision-making. 31,[40][41][42][43][44][45] The pandemic also disrupted patients' cancer care experiences. Individuals with cancer reported feeling isolated, having no or poor communication with their treating team, and limited involvement in clinical decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Farah et al ( 2021) [31] reported that pre-pandemic attempts to implement virtual technology were challenging. However, during the pandemic, the urgent need for alternate methods of communication quickly became evident.…”
mentioning
confidence: 99%